DEDIKASI SUPARNI DALAM DUNIA KEPESINDHENAN DI SURAKARTA - Riza Indri Hapsari; Rusdiyantoro Rusdiyantoro (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2022)
This study explains the factors that make up Suparni as a pesindhèn in the realm of Surakarta-style karawitan. Suparni became one of the senior sindhens who still exists in his world today. Therefore, youcan solvethe problem of Suparni's form factor into pesindhèn, namely by using Alvin Boskof's theory of social change f. Suparni's forming factors are divided into two, namely internal factors and external factors. The results of the research that has been carried out, it is known that theinternal actors in Suparni consist of creativity, talent, as well as traits and personalities. While external factors consist of the environment and its experience. It is these factors that have shaped Suparni as pesindhèn, even today.